Object-based attention in retaining binding in working memory: Influence of activation states of working memory. - He, Kaifeng; Li, Jiaofeng; Wu, Fan; Wan, Xueyi; Gao, Zaifeng; Shen, Mowei (Memory & Cognition, 2020)
It has been suggested that retaining bindings in working memory (WM) requires more object-based attention than retaining constituent features. Recent studies have found that when memorized stimuli are presented sequentially, the most recent stimulus is in a highly accessible privileged state such that it is retained in a relatively automatic and resource-free manner, whereas the other stimuli are in a non-privileged state. The current study investigated whether the activation states of WM modulate the role of object-based attention in retaining bindings in WM. To address this question, we presented three colored shapes sequentially and added a transparent-motion task (Experiment 1) or a mental rotation task (Experiment 2) into the WM maintenance phase to consume object-based attention. We consistently found that consuming object-based attention led to a larger impairment to bindings relative to constituent features, which is independent of the WM activation states, suggesting that object-based attention is critical in retaining bindings in WM across activation states of WM.